Taxation as tyranny: American Progress and the ultraconservative movement. (30th November 2018) - Huntington, John S.
Abstract : Willis E. Stone watched aghast as mid-century liberals expanded the size and power of the federal government. Stone, a former industrial engineer and unbending anti-statist, believed this liberal surge obfuscated and abetted an imminent red tide of communism. He founded the American Progress Foundation and its flagship periodical, American Progress, to spread a hardline libertarian message, hoping to spark conservative resistance against federal power. In the pages of American Progress, Stone and a coterie of other right-wingers published conspiratorial, anti-statist diatribes and promoted Stone's proposal, the Liberty Amendment, to repeal the Sixteenth Amendment. Right-wing business owners joined the fray, sponsoring American Progress through advertisements, and over time Stone's movement expanded to form a collaborative network with other far-right groups. This article illustrates how American Progress served as an activist and ideological nexus for the broader ultraconservative movement, which helped establish a hardline brand of libertarianism that reverberated throughout the modern American Right. Furthermore, by analysing the scope and influence of radical right-wing publications, this article provides a critical counterweight to the traditional left-wing focus of periodical studies.